1982
DOI: 10.1021/jm00351a008
|View full text |Cite
|
Sign up to set email alerts
|

New anticancer agents: synthesis of 1,2-dihydropyrido[3,4-b]pyrazines (1-deaza-7,8-dihydropteridines)

Abstract: Reaction of alpha-aminoacetophenone oximes (2) with ethyl 6-amino-4-chloro-5-nitropyridine-2-carbamate (1) gave ethyl 6-amino-5-nitro-4-[(2-oxo-2-phenylethyl)amino]pyridine-2-carbamate oximes (3), which were hydrolyzed under acidic conditions to give the corresponding ketones (4). Related pyridines substituted with a keto side chain were prepared from 1 and 1,3-diaminopropanone oximes and by oxidation of the side-chain hydroxy group of ethyl 6-amino-4- [[3-(N-methyl-N-phenylamino)-2-hydroxypropyl]amino]-5-nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Chemistry Compounds 15a-d were synthesized starting with the preparation of 2-amino-1-(4-hydroxyphenyl) ethanone hydrochloride 13 by Delépine reaction at low temperature, followed by condensation of carboxylic acids 14a-d in the presence of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDCI·HCl) and 1-hydroxybenzotriazole (HOBT) at room temperature 30,31) (Chart 1). 14a and d were converted into 16a and d in the presence of N,N′-carbonyldiimidazole (CDI) under an H 2 S atmosphere, and then 14a, d, 16a, and d were allowed to react with 2-bromo-4′-hydroxyacetophenone 11 in the presence of K 2 CO 3 32,33) (Chart 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemistry Compounds 15a-d were synthesized starting with the preparation of 2-amino-1-(4-hydroxyphenyl) ethanone hydrochloride 13 by Delépine reaction at low temperature, followed by condensation of carboxylic acids 14a-d in the presence of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDCI·HCl) and 1-hydroxybenzotriazole (HOBT) at room temperature 30,31) (Chart 1). 14a and d were converted into 16a and d in the presence of N,N′-carbonyldiimidazole (CDI) under an H 2 S atmosphere, and then 14a, d, 16a, and d were allowed to react with 2-bromo-4′-hydroxyacetophenone 11 in the presence of K 2 CO 3 32,33) (Chart 2).…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 22e-i were synthesized as shown in Chart 3, using a route nearly identical to that in Chart 1. 30,31) The amide 24 was prepared by condensation of carboxylic acid 14d and 1-(tertbutoxycarbonyl) piperazine 23 with EDCI·HCl as a condensation agent and 4-dimethylaminopyridine (DMAP) as a catalyst in CH 2 Cl 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[186] Structure-activity relationship studies indicated that the basic diaminopyridine is an essential structural requirement. [187,188] The fused dihydropyrazine increases the pyridine basicity and tolerates diverse substituents in positions 2 and 3. [189] Clinical trials with mivobulin (CI-980) showed that it lacks sufficient activity in the treatment of disseminated malignant melanoma [190] metastatic colorectal carcinoma [191] progressive malignant gliomas [192] and soft tissue sarcomas.…”
Section: Pyrido[34-b]pyrazinesmentioning
confidence: 99%
“…In view of the possibility that other benzoylphenyl ureas might possess higher and more selective antitumor activity compared to DFB, a study of analog screening was undertaken using B16 melanoma cells as an in vitro prescreen and B16 melanoma implanted subcutaneously (s.c.) in mice [9][10][11] as secondary screening. Because structure-activity relationships may be successful in designing novel selective inhibitors with improved chemotherapeutic potential [12][13][14][15], we examined the cytostatic activity of substituted 1-benzoyl-3-phenyl ureas with the following structural modifications: 1. Substitutions in the benzoyl ring (R).…”
Section: Introductionmentioning
confidence: 99%